Solution Sales Process Blueprinting (SSPB): A visual representation of value creating activities in sales process implementation - Ogundipe, Samuel Johnson (My University, 2015)
The dynamism and the increasing competition in the B2B market environment has forced many manufacturing organizations to transform their selling orientation and practices from purely product oriented sales to solution selling in order to maintain their competitive positions and adapt to the continuously changing customer’s needs. The transformation necessitates major changes within the organizations and also in its interactions with customers, most noticeably the sales process. Although, firms’ transition to solution providers is not a new phenomenon in sales literature, studies focusing on the changes in the sales process are fragmented. Additionally, most of the studies depicting the sales process have mainly concentrated on the different selling activities without incorporating the actors that are involved in the process, or visualizing the different customer touch-points, which are important in order to develop broader understanding of the firm selling practices and for identifying sources of opportunities. Therefore, by utilizing a process mapping techniques, known as blueprinting, this study contributes to existing knowledge by developing a sales process framework that visualizes different activities and customer touch-points in the sales process as well as actors carrying out those activities. A qualitative research method in the form of face-to-face interviews was utilized for collecting data from 8 Finnish manufacturing firms that are currently undergoing transitions to solution providers. Data analysis was carried out through a combination of within-case and cross-case analyses. The results show that firms are interacting with customers not only during the sales phase of the process, but also during manufacturing and post sales delivery to acquire and disseminate new information. However, the process blueprint that was developed in the research reveals the need for improvements in the firms’ sales process design, in order to better integrate the service function into the selling phase and to enhance the opportunities for post sales customer support.
Keywords: Solution Selling; Sales Process; Blueprinting; Relationship Selling; Customer Orientation.; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|; fi=Organisaatioiden viestintä|en=Communication in organizations|